Enablers and barriers of maternal and neonatal immunization programs in Latin America. (30th July 2021) - Ropero Alvarez, Alba Maria; Vilajeliu, Alba; Magariños, Mirta; Jauregui, Barbara; Guzmán, Lely; Whittembury, Alvaro; Cain, Emilia; Garcia, Odalys; Montesanos, Raul; Ruiz Matus, Cuauhtemoc; ,
Highlights: The Americas has a long history of maternal and neonatal immunization programs. Key enablers are high-level of political will and an immunization legal framework. National advisory bodies and pooled procurement facilitated vaccine introduction. To overcome barriers, need to focus on improving the "immunization journey". Strengthening MNI is an opportunity to improve maternal and neonatal health services. Abstract: Background: The Region of the Americas has a long history of implementing maternal and neonatal immunization (MNI) programs. Our study aimed to understand the state of MNI policies, strategies and implementation practices in Latin America (LA). Methods: Study conducted in 5 middle-income countries: Argentina, Brazil, Honduras, Mexico and Peru. The methods included a desk review, interviews with national stakeholders and health care providers, focus groups with pregnant women and observations in health facilities. Enablers and barriers were identified and categorized as individual, societal or related to the health system. Results: All 5 participating countries had similar MNI policies and high access to antenatal care. Key enablers were the high acceptability of vaccination during pregnancy, high-level of political will and a national legal framework ensuring free access to vaccines. At the health system level, implementation was facilitated by the existence of immunization advisory committees, a pooled vaccine procurement mechanism, complementary vaccine delivery strategies, conditional cash transfer to users and performance incentives to health facilities. The main programmatic barriers were the lack of adequate MNI information; limited coordination between antenatal and immunization services; inadequate supply, resources and infrastructure; high staff turnover; insufficient training for health care providers; and weak monitoring and reporting systems. Conclusion: Middle-income countries in LA have successfully implemented MNI programs and several enablers were identified. To overcome remaining barriers, there is a need to focus on improving the "immunization journey" for pregnant women through providing more clear and timely information to users and providers; removing barriers to access; ensuring adequate supply, human resources and infrastructure; making the health service experience positive; and establishing integrated information systems that allow for monitoring the progress toward achieving MNI goals. Strengthening the MNI programs can also improve equitable access to health services and prepare for the introduction of future vaccines for pregnant women.